Efektifitas Pelatihan Berpikir Positif untuk Menurunkan Kecemasan dalam Menghadapi Ujian Nasional (UN) pada Siswa SMA - Pangastuti, Maya (Persona:Jurnal Psikologi Indonesia, 2014)
Abstract. This study aims to test the effectiveness of positive thinking training to reduce anxiety in the face of National Examination in high school students. Subjects in this study were students of class XII SMA Negeri 1 Badegan, Ponorogo, East Java who experience anxiety facing the National Exam. Subjects consisted of 21 students the experimental group and a control group of 17 students. National Exam anxiety scale face scale used was tested validity and reliability. The research method used was Randomized Pretest-Posttest Control Group Design. One way ANOVA test results obtained by the pretest and posttest experimental group with p = 0.000 (p <0.01), meaning that positive thinking training is proven to reduce anxiety in the face of National Examination in class XII school.Keywords: Anxiety facing the National Exam, Training of Positive Thinking